Association between menopause-related symptoms and muscle mass index among perimenopausal and postmenopausal women and the mediating role of estrogen levels - Wang, Xiaoyi; Yang, Dongjian; Li, Jiahui; Jin, Lei; Xia, Shuhua; Jin, Furui (Frontiers in Endocrinology, 2025)
BackgroundThe decline in muscle mass is a common concern among perimenopausal women. However, the association between menopause-related symptoms and muscle mass remains inconclusive, and the mechanistic role of estrogen is still unclear.MethodsThe study included 407 peri- and postmenopausal women aged 40–60 years who visited the International Peace Maternity and Child Health Hospital. Menopausal symptoms were assessed using the modified Kupperman Index (KMI). Muscle mass was evaluated using the InBody 270 analyzer, and sex hormone levels were determined by chemiluminescent immunoassay. Multiple linear regression and Mediation analysis were conducted to examine the association of KMI with MMI and the mediation of estrogen.ResultsA total of 407 valid cases were collected. The mean age of the patients was 49.96 ± 3.25 years, with an average body weight of 58.02 ± 7.36 kg and an average BMI of 22.50 ± 2.61 kg/m². The findings showed that advanced age, lower education level, and reduced muscle mass index (MMI) were linked to elevated KMI scores (p<0.05). Patients with hypertension had higher KMI scores (p<0.05). Additionally, decreased estradiol (E2) levels correlated with heightened menopausal symptoms (p<0.05). After controlling for confounding factors such as age, educational level, menopausal stage, history of hypertension, follicle-stimulating hormone (FSH), and E2, KMI was negatively correlated with MMI (β=-1.612, 95% CI: -2.677 to -0.546, p=0.003). Specifically, for each unit increase in MMI, KMI decreased by 1.612 points (R²=0.186, p=0.003). Stratified analysis showed that the negative correlation between KMI and MMI was significant only in premenopausal women. Both the direct and indirect effects of MMI and E2 on KMI were statistically significant (p<0.01). The mediating effect of MMI on KMI through E2 accounted for 26.9% (p=0.001).ConclusionsLower muscle mass is associated with severe menopausal symptoms, partially mediated by estrogen. Maintaining muscle mass may alleviate symptoms, highlighting the importance of resistance training and hormone regulation in perimenopausal women. However, due to the cross-sectional nature of the study, causality cannot be inferred. Longitudinal or interventional studies are warranted to further validate these associations and explore underlying mechanisms.